2018
DOI: 10.1128/mra.01050-18
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of the Nitrate-Dependent Iron-Oxidizing Proteobacteria Acidovorax sp. Strain BoFeN1 and Paracoccus pantotrophus Strain KS1

Abstract: The draft genomes of the nitrate-dependent iron-oxidizing bacteria Acidovorax sp. strain BoFeN1 and Paracoccus pantotrophus strain KS1 are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Hence, the vivianite mineral surfaces themselves seem to catalyse the abiotic reaction between NO − 2 and Fe(II)/Fe 2+ (the stimulation of Fe-dependent nitrite reduction may also be attributed, in part, to vivianite dissolution providing ample Fe(II) substrate). Previous studies have reported on mineral-enhanced chemodenitrification (Dhakal et al, 2013;Grabb et al, 2017;Klueglein and Kappler, 2013;Rakshit et al, 2008), and the catalytic effect may be due to NO − 2 adsorption onto the minerals' surface possibly facilitating a direct electron transfer. Similar findings have previously been reported on Fe(II) oxidation promoted by electron transfer during adsorption onto an Fe(III) minerals' surface (Gorski and Scherer, 2011;Piasecki et al, 2019).…”
Section: Surface Catalysis Of Chemodenitrificationmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence, the vivianite mineral surfaces themselves seem to catalyse the abiotic reaction between NO − 2 and Fe(II)/Fe 2+ (the stimulation of Fe-dependent nitrite reduction may also be attributed, in part, to vivianite dissolution providing ample Fe(II) substrate). Previous studies have reported on mineral-enhanced chemodenitrification (Dhakal et al, 2013;Grabb et al, 2017;Klueglein and Kappler, 2013;Rakshit et al, 2008), and the catalytic effect may be due to NO − 2 adsorption onto the minerals' surface possibly facilitating a direct electron transfer. Similar findings have previously been reported on Fe(II) oxidation promoted by electron transfer during adsorption onto an Fe(III) minerals' surface (Gorski and Scherer, 2011;Piasecki et al, 2019).…”
Section: Surface Catalysis Of Chemodenitrificationmentioning
confidence: 98%
“…One redox pair that has been proposed to be exploited by microbes under anoxic conditions through a mechanism known as nitrate-dependent Fe(II) oxidation (NDFeO) is NO − 3 /Fe 2+ (Ilbert and Bonnefoy, 2013;Straub et al, 1996). To date, genetic evidence that clearly supports this metabolic capacity of the studied microorganisms remains lacking (Price et al, 2018), and biogeochemical evidence is rare and putative. The latter is mostly based on experiments with the chemolithoautotrophic culture KS, which is a consortium of four different strains, including a relative of the microaerophilic Sideroxydans/Gallionella.…”
Section: Introductionmentioning
confidence: 99%
“…Under all treatments, Acidovorax and Chlorobium were observed as dominant IOB. Members of Acidovorax, such as strains BoFeN1 and 2AN, are neutrophilic, nitrate (NO 3 − )-reducing, and Fe 2+ -oxidizing bacteria in anaerobic environments [41,42]. Therefore, NO 3 − reduction would also play a role in Fe oxidation in the simulated lake system.…”
Section: Key Taxa and Predicted Functions Of Bacteria Associated With...mentioning
confidence: 99%
“…12 In addition, some heterotrophic denitrifying bacteria are able to catalyze Fe(II) oxidation, in a process known as nitrate-dependent iron(II) oxidation (NDFO), which is thought to be a result of both biotic and indirect biotic effects, 13 although, the mechanism of Fe(II) oxidation in these heterotrophs is not fully resolved, and no enzymatic Fe(II) oxidation has been reported to date. 14,15 Moreover, nitrite, or most likely its selfdecomposition products, NO and NO 2 can abiotically oxidize Fe(II). 16 These reactive nitrogen species are also intermediary compounds produced and accumulated during denitrification, 17 and have been shown to be responsible for most of the Fe(II) oxidation observed.…”
Section: Introductionmentioning
confidence: 99%